Burnout prevalence in medical students attending a team-based learning school - Kushida, Simone Sayuri; Troster, Eduardo Juan (Frontiers in Education, 2023)
Introduction: Worldwide burnout prevalence among medical students is high. It has a negative impact in student’s personal and professional lives with commitment of psychosocial wellbeing and academic performance. It can result in physicians with emotional distancing and indifference to work, and compromises the quality of health offered to society. This study evaluates burnout in medical students selected by Mini Multiple Interviews (MMI) and that who were being taught by Team-based learning (TBL) method. MMI are often used to select students with soft skills for Medicine and TBL is related to greater academic achievement, which would allow student to have greater resilience to stress. Information on burnout occurrence is lacking for this type of students. Methods: Students (143) attending the first three semesters at a private medical school were evaluated. The Copenhagen Burnout Inventory - Student Version (CBI-SV) questionnaire was applied on three occasions (applications=Apps one, two and three) in each semester. Scores ≥ 50 were considered as burnout. Data were analyzed by statistics programs. Results: Personal-related and study-related burnout frequencies for 1st semester students were respectively 24.4% and 22% in App one, and rose to 51% and 48.5 % at the semester’s end. Second- and third-semester students’ frequencies reached 80.4% and 78.8%. Around 40% of 1st semester students having burnout at App one maintained the burnout score. Peer- and teacher-related burnout frequencies were low (4.9% and 2.4%) at the1st semester App one and rose to highest (24-30%) by the end of the 2nd semester. Female students had significantly higher burnout frequencies in personal (p <0.001) and study-related burnout subscales (p=0.003). Students living with friends had lower study-related burnout scores than those living with family or alone (p=0.024). There were no significant correlations between burnout scores and tuition funding (partial or total), and having or not religious faith. Conclusions: The prevalence of personal and study-related burnout in FICSAE medical students, MMI-selected and TBL-taught, was similar to those internationally reported. College semester and female gender were associated with worse burnout levels. Additional studies are needed to support more effective actions to reduce the stress impact on the students.